2016
DOI: 10.3390/antibiotics5040038
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Response of 30S-bound IF3 to A-Site Binders Streptomycin and Kanamycin

Abstract: Aminoglycoside antibiotics are widely used to treat infectious diseases. Among them, streptomycin and kanamycin (and derivatives) are of importance to battle multidrug-resistant (MDR) Mycobacterium tuberculosis. Both drugs bind the small ribosomal subunit (30S) and inhibit protein synthesis. Genetic, structural, and biochemical studies indicate that local and long-range conformational rearrangements of the 30S subunit account for this inhibition. Here, we use intramolecular FRET between the C- and N-terminus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…An increase in time of donor fluorescence indicates that IF3 domains are moving apart and, vice versa , a decrease of the observed fluorescence indicates that the domains are getting close to each other (Supp. Fig 1) [23]. Binding of IF3 DL to the 30S ribosomal subunit resulted in an increase of fluorescence, consistent with the factor transiting from a closed conformation in solution to a more opened one while bound to the 30S subunit (Fig 2A).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…An increase in time of donor fluorescence indicates that IF3 domains are moving apart and, vice versa , a decrease of the observed fluorescence indicates that the domains are getting close to each other (Supp. Fig 1) [23]. Binding of IF3 DL to the 30S ribosomal subunit resulted in an increase of fluorescence, consistent with the factor transiting from a closed conformation in solution to a more opened one while bound to the 30S subunit (Fig 2A).…”
Section: Resultssupporting
confidence: 70%
“…To monitor the conformational rearrangements of IF3, we used a fluorescent derivative of the factor harboring donor and silent acceptor dyes specifically linked to the N and C terminal domains, respectively (Fig1, inset) [23]. Double-labeled IF3 (IF3 DL ) allows to monitor intramolecular FRET changes resulting from the movement of IF3 domains with respect to each other.…”
Section: Resultsmentioning
confidence: 99%
“…However, IF-3 was found to be underrepresented on the mutant鈥檚 30S compared to the wild-type strain, and this protein is known to stabilize the transiently recycled 30S subunits by preventing reassociation into 70S in E. coli ( Hirokawa et al, 2005 ). Studies in M. tuberculosis showed that kanamycin and streptomycin both affect the positioning of the IF-3 on the 30S platform and the overall dynamics of 30S association with the IF-3, thus perturbing the translation initiation ( Chulluncuy et al, 2016 ). Low abundance of IF-3 on the mutant鈥檚 ribosomes may indicate that these 30S ribosomal subunits remain in conformation, thus favoring the inhibition of translation by aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent measurements were carried out at 22 藲C using a monochromatic light source (470 nm) powered with 10 mA. Emitted fluorescence was measured with photomultipliers set at 320 V after passing a long-pass filter with a cut-off of 515 nm essentially as described in [35]. Equal volumes (60 渭L) of each reactant were rapidly mixed and fluorescence changes over time were measured.…”
Section: Methodsmentioning
confidence: 99%